The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1187/cbe.21-10-0305
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and Contact Frequency Promote Mentorship Quality among Hispanic Undergraduates in STEM

Abstract: This study tests the process-oriented mentorship model (POMM) regarding how mentor–protégé similarities and the moderating role of contact frequency influence mentorship quality, coauthoring experiences, and STEM career persistence intentions among faculty-mentored Hispanic STEM majors in their senior year of college.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…This finding indicates that the TAD framework might benefit from explicit attention to interpersonal match between mentors and mentees because mentors who perceive their mentees as similar to them may provide more guidance and resources that support their mentees’ competence development. Indeed, prior research has shown the importance of deep‐level similarity, meaning shared values and culture, for promoting high‐quality STEM mentoring relationships 17–19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicates that the TAD framework might benefit from explicit attention to interpersonal match between mentors and mentees because mentors who perceive their mentees as similar to them may provide more guidance and resources that support their mentees’ competence development. Indeed, prior research has shown the importance of deep‐level similarity, meaning shared values and culture, for promoting high‐quality STEM mentoring relationships 17–19 …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, prior research has shown the importance of deep-level similarity, meaning shared values and culture, for promoting high-quality STEM mentoring relationships. [17][18][19]…”
Section: Undergraduate Researcher Characteristicsmentioning
confidence: 99%
“…Moreover, higher levels of mentor-mentee psychological similarity lead to higher levels of psychosocial support, relationship satisfaction, and publications, (i.e. Hispanic trainees with a Hispanic faculty mentor report engaging in more coauthoring opportunities than peers with non-Hispanic mentors) [16]. Some institutions have required diversity and/or implicit bias trainings for their staff, trainees, and faculty.…”
Section: Discussionmentioning
confidence: 99%
“…We have also codified advice from postdoctoral trainees on pursuing a research career in academia, and one of the top recommendations was finding a strong mentor [5]. Trainees from URGs do not often find mentors that match their identity, and it has been shown that higher levels of mentor-protégé psychological similarity are related to higher levels of psychosocial support and relationship satisfaction [15, 16]. Overall, mentorship at the postdoctoral stage remains key for increasing workforce and faculty diversity [17].…”
Section: Introductionmentioning
confidence: 99%
“… 2017 , Pedersen et al. 2022 ). However, similarity does not always translate to academic outcomes (Robinson et al.…”
Section: Integrating Into Stem Professional Communitymentioning
confidence: 99%